Systemic nanoparticle delivery of CRISPR-Cas9 ribonucleoproteins for effective tissue specific genome editing - Tuo Wei (Nature Portfolio, 2020)
Therapeutic targets of CRISPR-Cas can often not be accessed due to lack of carriers to deliver RNPs systematically. Here, the authors engineer modified lipid nanoparticles for delivery of gene editing proteins to specific tissues.